Selection and connection: the impact of internet use on the depression of Chinese older adults - Jiao, Kaishan; Sun, Yue (Frontiers in Public Health, 2025)
IntroductionInternet usage has significant effects on the mental health of older adults, particularly in reducing depression levels. However, its impact may differ based on factors such as internet usage frequency, purposes, gender, and urban-rural residence. This study aims to examine the differential effects of internet use on depression among older adults, exploring the mediating role of social networks in these relationships.MethodsBased on panel data from the 2018 and 2020 China Longitudinal Aging Social Survey, a fixed-effects model was employed to systematically analyze the impact of internet use (including whether they use the internet, frequency of use, and purposes of use) on the mental health of older adults. The mediating role of social networks (family networks and friend networks) was tested using the Bootstrap method.ResultsThe study found that internet use significantly reduces depression levels among older adults (coefficient = −0.440, p < 0.001), with notable differences in mental health benefits based on gender and urban-rural residence. Both family networks and friend networks mediate the relationship between internet use and depression. Specifically, older adults who use the internet frequently or for interpersonal communication tend to expand their social networks, which in turn improves their mental health. Family networks exhibit a stronger mediating effect compared to friend networks. However, the positive effects of leisure and information-seeking internet activities are partially offset by the reduction in social network size.DiscussionThis study highlights the complex relationship between internet use, social networks, and mental health in older adults. Significant gender and urban-rural differences exist in the impact of internet use on depression among older adults, indicating the need for tailored interventions. The findings also emphasize the importance of promoting internet use for social purposes while being mindful of the potential negative impacts of excessive digital engagement among older adults, particularly in rural areas. Additionally, social networks, especially friend networks, play an important role in enhancing the mental health benefits of internet use for older adults.